Contributions, bias, and research gaps in large animal ex vivo lung perfusion models: A systematic review - Shane Fisher; James O’Connor; Karen Redmond (JHLT Open)
Background: A major challenge in lung transplantation is the shortage of viable donor lungs. Ex vivo lung perfusion (EVLP) has emerged as an effective assessment and conditioning tool to expand the donor lung pool. This systematic review sought to establish the contribution of large animal models to EVLP development and application, particularly focusing on assessing the risk of bias and the certainty of evidence. Methods: A strategic literature search was conducted using a predefined pro forma. Relevant data were extracted, and thematic analysis was applied for qualitative synthesis of key measures. Methodological quality and bias risk were assessed using systematic review centre for laboratory animal experimentation’s risk of bias tool, and certainty of evidence was evaluated using the grading of recommendations assessment, development and evaluation Framework. Results: A total of 32 studies met the inclusion criteria, using porcine, ovine, rabbit, and canine models. Key themes included EVLP’s role in donor lung assessment and preservation, marginal donor lung repair, and as an experimental translational platform. All studies were assessed with the systematic review centre for laboratory animal experimentation tool and had a high or unclear risk of bias. Twenty-eight (87.5%) showed low certainty of evidence, 2 (6.25%) very low, and 2 (6.25%) moderate, raising concerns about overall evidence strength. Conclusions: Large animal EVLP models have significantly advanced donor lung preservation, reconditioning, and therapeutic intervention. However, methodological bias remains a concern due to inconsistent adherence to reporting and procedural standards. Greater conformity to standardized protocols is pivotal to improve the reliability, reproducibility, and translational value of future EVLP research.